Job satisfaction of nurses in a public hospital with a high number of HIV and AIDS patients - Hennessy, Elaine (My University, 2009)
The purpose of this research was to investigate job satisfaction and the impact of HIV and AIDS on nurses in a public hospital in Gauteng. The problems that generated this study included absenteeism, low morale and negativity of nurses working with patients in the presence of the HIV/AIDS crisis. A quantitative research method was used. The sample size comprised 248 nurses from all categories. The Measure of Job Satisfaction was the framework used which covers issues such as remuneration, security, growth, social and supervisory aspects. The framework for the HIV/AIDS section of the research was the Government policy on HIV/AIDS. Results showed job satisfaction was adversely affected by staff shortages, workload, frustrations with management, remuneration, lack of developmental opportunities and equipment. Analysis of the open-ended responses showed ambivalence amongst nurses towards nursing HIV/AIDS patients. Some expressed sadness and fear while others found their caring role fulfilled. The study indicated that facilitating development of staff, improving management skills, providing staff and equipment will all impact positively on job satisfaction. In addition, a deliberate effort needs to be made to plan debriefing/counselling services for nurses as well as ongoing HIV training.
M.Sc.(Nursing), Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: job satisfaction; nurses; HIV/AIDS patients; public hospital